A study of employee empowerment in enhancing work performance: case study at Century Mahkota Hotel, Melaka - Muhamad, Zambahari (2004)
Most people have heard about employee empowerment and have general idea of what the word means. Empowerment means managers or top level management enables their employees to greater responsibilities and authority. The result will be increasing in employee’s work performance. The problems or obstacles that occur in the empowerment process together with the supporting systems that help to contributed to the effective empowerment also determined. A sample of 50 employees was given the questionnaires. The studies try to find the relationship between employee empowerment and work performance, problems or obstacles that prevent from effective empowerment and factors that support the process. Instead of self-administered questionnaires, other methods of research that have been used in this study are data collection and Statical Package for Social Science (SPSS). The finding is hopefully can contribute and help this hotel in order to increasing employees work performance at the workplace.